Confinement to the intrapancreatic bile duct is independently associated with a better prognosis in extrahepatic cholangiocarcinoma - Ahn, Keun Soo (BMC Gastroenterol, 2016)
BACKGROUND: Actual differences of long term outcome of extrahepatic cholangiocarcinoma according to the location of the tumor have not yet been studied. The aim of this study was to evaluate the prognosis and optimal surgical procedure for middle (BD) cancer. METHODS: Among 109 patients with carcinoma of the extrahepatic BD underwent surgical resection, curative resection of extrahepatic BD cancer was performed in 90 patients. They were classified into three groups according to the location of tumors: DISTAL (n = 32), tumor was confined to the intrapancreatic bile duct; MID (n = 20), tumor was located between below the confluence of the hepatic duct bifurcation and suprapancreatic portion of the BD; and DIFFUSE (n = 38), tumor was located diffusely. RESULTS: Tumor involving the middle BD (MID or DIFFUSE) had a higher rate of perineural invasion as compared to the DISTAL group. The overall and disease-free survival rate for the MID or DIFFUSE group was significantly worse than that of DISTAL. In the MID/DIFFUSE group, there was no significant difference of survival according to the type of the operation (pancreaticoduodenectomy or segmental BD resection). The multivariate analysis showed that tumor involving middle BD (MID or DIFFUSE group) and node metastasis were independently poor prognostic factors for the disease free and overall survival. CONCLUSION: Extrahepatic cholangiocarcinoma involving the extrapancreatic BD has a worse prognosis than those confined to the intrapancreatic BD. In patients with tumors confined to the middle BD, BD resection can be considered as an alternative surgical procedure to pancreaticoduodenectomy, if an R0 resection can be accomplished.